HUBUNGAN KOMUNIKASI TERAPEUTIK DAN POLA MAKAN DENGAN KEJADIAN GASTRITIS DI PUSKESMAS UJUNG KARANG BENGKULU TENGAH - ANDARI, FATSIWI NUNIK; Yulianda, Yuni (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2021)
Gastritis is one of the diseases that need more attention. Uncaring gastritis would affect the occurrence of bleeding in the gastrointestinal tract, ulcers, perforation, and anemia. The purpose of this study was to determine the relationship between therapeutic communication and dietary habits with the incidence of gastritis in the Public Health Centre of Ujung Karang, Bengkulu Tengah. This research was a quantitative study with a case-control design. The total sample was 140 patients that were divided into two groups: 70 respondents were in the case group and 70 respondents were in the control group. The results of this study indicate that 60,7% of respondents received a good communication therapeutic and 39,3% of respondents stated the communication therapeutic was poor. Based on eating habits, 62,1% had a regular diet on the eating frequency and 37,9% was not. For the type of food consumed by the respondents, 41,4% of respondents had consumed unhealthy food. Based on the chi-square statistical test, there was a significant correlation between therapeutic communication and eating habits with the incidence of gastritis. Keywords: eating habits, gastritis, therapeutic communication